Mechanical properties of raw bamboo fiber-reinforced phosphogypsum-based composite cementitious materials and their strengthening mechanism - Xian Fu; Peng Liu; Dewen Kong; Yuan Li; Yongfa Wang (PLoS ONE, 2025)
Phosphogypsum-based cementitious materials (PGCs) typically exhibit low strength and poor toughness when utilized as construction materials. This study explores the incorporation of raw bamboo fibers of varying lengths into PGCs at different ratios to develop raw bamboo fiber-reinforced phosphogypsum-based composite materials (BFRPGCs). Firstly, the influence of the water-cement ratio on the mechanical properties of BFRPGCs was investigated through a one-factor experimental approach, leading to the identification of an optimal water-cement ratio. Secondly, the effects of the length and content of raw bamboo fibers on the mechanical properties of BFRPGCs at this optimal water-cement ratio were examined, along with an exploration of the mechanisms by which raw bamboo fibers impact the mechanical properties of the composites, considering their damage modes. Finally, the microstructure of BFRPGCs was analyzed using scanning electron microscopy (SEM), which elucidated the mechanisms through which raw bamboo fibers influence the working and mechanical properties of the composites. The results demonstrated that the incorporation of raw bamboo fibers significantly enhanced the mechanical strength of the specimens. Specifically, when the length of the bamboo fibers was 12 mm and the doping amount was 1.0%, the compressive and flexural strengths of BFRPGCs reached their maxima at 28.99 MPa and 8.41 MPa, respectively. These values represent increases of 123.73% and 169.82% compared to the control group. Additionally, hydration-generated calcium silicate hydrate (C-S-H) gels and calcium aluminate (AFt) phases formed a skeletal support around the CaSO₄·2H₂O, reinforcing the matrix structure. Furthermore, numerous hydration products adhered to the surfaces of the raw bamboo fibers, resulting in enhanced adhesion between the fibers and the matrix. This study provides valuable insights for the research and application of fiber-reinforced phosphogypsum-based building materials.